Isolation and identification of fungi causing post-harvest spoiled mango fruits vended in Hanoi, Vietnam - Tam, Dang Thi Thanh; Trang, Do Huyen; Thanh Huyen, Nguyen (Vietnam Journal of Biotechnology, 2024)
Mango (Mangifera indica L.) is one of the most popular and nutritious fruits cultivated widely in Vietnam. However, under increasingly harsh climate conditions, mangoes are easily susceptible to fungal invasion and spoiled, thereby reducing mango yield. Therefore, this study was carried out to determine the pathogenic fungal strains of mango to provide useful information for finding effective measures to prevent the diseases. Rotten mango fruits were collected from different markets in Hanoi, Vietnam. Three fungal strains (M1, M2 and M3) were isolated from the studied mangoes samples. All strains were demonstrated as fungal agents associated with mango rot through pathogenicity tests. Microscopic observation showed that the mycelium of these fungal strains was branched and septate. M1 strain formed dark-brown conidiophores and conidia produced on conidiophores. M2 strain produced α- and β-conidia, as well as sub-ovoid and brown sclerotia. Whereas the M3 strain could not produce spores. Additionally, this study determined that all three fungal isolates showed the fastest growth on PDA at 30oC. The optimum growth of the M1 and M3 strains was observed at pH 5.0 while the M2 strain grew actively at pH 7.0 and 8.0. All selected strains showed the ability to produce extracellular enzymes, in which the M1 strain synthesized both cellulase and pectinase while the M2 and M3 strain secreted only pectinase. Finally, by molecular identification method, the isolates (M1, M2 and M3) were identified as Aspergillus niger isolate M1, Phomopsis sp. M2, Lasiodiplodia theobromae M3, respectively.